Persepsi Mahasiswa Tentang Efektivitas Pembimbingan Akademik - Jalal, Novita Maulidya; Abdullah, Edi; Nadjamuddin, Lukman (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
The purpose of this study was to determine how students' perceptions of the effectiveness ofacademic guidance (PA). The research method used is a one shot case study. The data werecollected using a survey related to perceptions, then analyzed quantitatively with the percentagetechnique. Subjects were 102 students who were willing to take part in the research. The resultsof the study were 40.2% of the subjects felt that they were effective. The process of academicguidance so far is that 93.1% are generally known to function when they consult during KRSan,and 20.6% of subjects who consult related to personal (non-academic) problems. Thus it can beconcluded that Faculty X Makassar students perceive the role of mentoring PA tends towardsacademic guidance and has not been perceived as non-academic guidance.